Temperature Impact on Magnesium Isotope Fractionation in Cultured Foraminifera - Dämmer, Linda K.; van Dijk, Inge; de Nooijer, Lennart; van der Wagt, Bas; Wilckens, Frederike K.; Zoetemelk, Bridget; Reichart, Gert-Jan (Frontiers in Earth Science, 2021)
Element incorporation in shell calcite precipitated by foraminifera reflects the chemical and physical properties of the seawater the foraminifera lived in and can therefore be used to reconstruct paleo environmental conditions. One of the most prominent proxies for past seawater temperature is Mg/Ca of foraminiferal calcite. Still, in addition to seawater temperature, also biomineralization processes impact foraminiferal Mg/Ca values. As the impact of biomineralization plays a major role and is not necessarily constant, it is imperative to identify the mechanism by which Mg is incorporated and thereby understand how temperature influences Mg incorporation. Biomineralization is discriminating against Mg to different degrees and hence investigating the fractionation of Mg isotopes at different temperatures and for species with contrasting calcification pathways can be used to better understand the pathway of Mg during biomineralization. Overall, we observe that foraminifera with higher Mg content have δ26Mg values closer to those of seawater. Moreover, controlled temperature culture experiments show that parallel to an increase in Mg/Ca, δ26Mg in the tests of large benthic foraminifer Amphistegina lessonii decreases when sea water temperatures increase. This negative correlation between shell Mg/Ca and δ26Mg suggests a two-step control on the incorporation of Mg during biomineralization. Using a simple model, we can explain both trends as a result of a stable Mg pool, which is only little fractionated with respect to sea water and a temperature dependent Mg pool which shows a higher fractionation with respect to sea water during biomineralization. The stable, not much fractionated pool is relatively large in high Mg foraminifera, whereas for the low Mg foraminifera the transport of Mg over a cell membrane probably results in the observed inverse correlation. Here we present a model using the Mg isotope fractionation we established for A. lessonii to explain the general trends for both high- and low-Mg/Ca foraminifera. A process-based understanding remains crucial a robust interpretation of foraminiferal Mg-isotopes.